A Scoping Review on the Attributes of Cluster Randomized Controlled Trials in Long-Term Care Facilities. (22nd January 2020) - Kraut, Roni Y.; Katz, Lauren S.; Babenko, Oksana; Diaz Carvallo, Fabiola; Alexanders, Roberto; Chan, Derek S.; Campbell, Sandy; Eurich, Dean T.; Garrison, Scott
Abstract : Cluster randomized trial design, where groups of participants are randomized instead of individual participants, is increasingly being used in long-term care research. The purpose of this review was to determine the characteristics of cluster randomized trials in long-term care facilities. A medical librarian conducted the literature search. Two independent reviewers reviewed each paper. Studies were included if the design was cluster randomized and participants were from long-term care facilities. For each included study, two independent data extractors captured data on study attributes, including: journal, location, year published, author discipline, funding, methodology, number of participants, and intervention target. The literature search yielded 7, 679 unique studies, with 195 studies meeting the selection criteria and being included for data extraction. The included studies were published between 1976 and 2017, with 53% of studies published after 2009. The term cluster randomized was in the title of only 45% of the studies. The studies were conducted worldwide; the United States had the largest number of studies (23%), followed by the United Kingdom (18%). Ten percent of studies were published in journals with an impact factor >10. The most frequent discipline of the first and last authors was medicine (34%), followed by nursing (17%). Forty-nine percent of the studies had government funding, while only 20% had medical industry funding. In studies with <1000 residents, 85% of the studies obtained consent from the resident and/or their proxy, while in studies with ≥ 1000 residents, it was 31%. The most frequent intervention targets were infection (13%), falls/fracture (13%), and behavior/physical restraint (13%). Cluster randomized controlled trials in long-term care have a unique set of characteristics. Results of this review will provide guidance to researchers conducting studies in long-term care facilities.